Parents’ Efforts in Incorporating Anti-Hedonistic Values in Adolescents - Khalimahtus Sakdiah; Ikhwan Aziz Q (Journal of Contemporary Islamic Education, 2025)
The phenomenon of a hedonistic lifestyle among urban adolescents shows a worrying trend, especially in the context of social transformation in the digital era. This study aims to examine the role of parents in instilling anti-hedonistic life values in adolescents in Metro City. A qualitative approach with a case study type was used to explore in-depth forms of role modeling, internalizing spiritual values, and social control strategies within the family environment. Data were obtained through in-depth interviews, participant observation, and documentation, then analyzed using an interactive model. The results show that parents play an active role through three main approaches: first, role modeling in living a simple life that instills the values of contentment and asceticism; second, habituating worship and positive behavior from an early age that strengthens children's moral and spiritual awareness; and third, social control based on dialogue and trust that creates an educational climate within the family. These three strategies have effectively fortified adolescents from consumer culture's influence and formed independent, resilient, and religious characters. This study emphasizes the importance of the family as the primary institution in character education based on Islamic values amidst the challenges of modernity and globalization.